Clinical characteristics and prognostic risk factors of healthcare-associated pneumonia in a Korean tertiary teaching hospital. Issue 42 (October 2017) - Ahn, June H.; Lee, Kwan H.; Chung, Jin H.; Shin, Kyeong-Cheol; Lee, Choong K.; Kim, Hyun Jung; Choi, Eun Young
Abstract : Abstract: The 2016 American Thoracic Society and Infectious Diseases Society of America (ATS/IDSA) guidelines removed the concept of healthcare-associated pneumonia (HCAP). We examined whether the 2016 ATS/IDSA guidelines are applicable in Korea. We conducted a retrospective, observational study of pneumonia patients who were hospitalized at a tertiary teaching hospital from March 2012 to February 2014. Identified pathogens that were not susceptible to β-lactams, macrolides, and fluoroquinolones were defined as community-acquired pneumonia drug-resistant pathogens (CAP-DRPs). We analyzed the risk factors for 28-day mortality and the occurrence rate of CAP-DRPs. Of the 1046 patients, 399 were classified with HCAP and 647 with CAP. HCAP patients were older and had more comorbidities than CAP patients. Initial pneumonia severity index (PSI) was higher in patients with HCAP than with CAP. HCAP was associated with not only an increased rate of CAP-DRPs (HCAP, 19.8%; CAP, 4.0%; P  < .001) but also an increased rate of inappropriate initial antibiotic therapy (IIAT) (HCAP, 16.8%; CAP, 4.6%; P  < .001). HCAP was also associated with an increased 28-day mortality rate compared with CAP (HCAP, 14.5%; CAP, 6.3%; P  < .001). In a multivariable analysis, PSI was an independent risk factor for 28-day mortality in HCAP patients (odds ratio 1.02, 95% confidence interval 1.01–1.04). CAP-DRPs and IIAT were not associated with mortality. Patients with HCAP revealed higher rates of CAP-DRPs, IIAT, and mortality than patients with CAP. However, CAP-DRPs and IIAT were not associated with mortality. PSI was the main predictive factor for 28-day mortality in patients with HCAP.